O uso da ferramenta App Inventor no ensino de programação em cursos de TI - Nascimento, Robertson da Silva (2023)
With the increase in demand for admission to undergraduate courses in Information Technology (IT), the current scenario of IT education faces some challenges. One of them is the inequality between the level of programming knowledge that students have when they arrive at university. Due to the fact that there are students who already have experience with software development, even with graphical interfaces, while others do not even know the definition of an algorithm, early discouragement may occur in this second group. In this way, based on the fact that it is necessary to use alternative means of teaching programming, which stimulate students more, by enabling the creation of mobile applications that are more similar to those in the current market, this work carried out an experiment with a group of students degree in the IT field. Using the App Inventor block programming tool, video classes were then created, as well as auxiliary study material, which were consumed by a group of students. This group, along with a second group that did not consume such materials, were then subjected to judgment tests on block programming use, and programming ability. Based on the results collected from these tests, a comparison and analysis between the two groups was carried out. After this analysis, similar results were concluded between the groups, however, with the group consuming the materials doing a little better.